2015
DOI: 10.1590/1678-4162-8070
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the proximal tibial angles between Labrador Retrievers and other dog breeds with and without cranial cruciate ligament rupture

Abstract: The influence of the proximal tibia conformation in the rupture of the cranial cruciate ligament (CCL) in dogs is still controversial, especially in Labrador Retrievers. The aim of this study was to compare the angles of the proximal tibia between Labrador Retrievers and other large breeds of dogs, both groups with and without CCL rupture. Radiographic images of 64 stifle joints were obtained and divided into four groups of 16 images. Group 1 consisted of Labrador dogs without orthopedic disorders, group 2 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the current study, with the intention to develop a more accurate method to evaluate the lever arm of the extensor mechanism, the PLIA was measured and ratio of the lengths of the lines (X/Y) was calculated to allow for the comparison of values between animals of different sizes (Arruda et al 2015). Theoretically, a longer patellar tendon lever arm will lower the required strength of the quadriceps to move the tibia and promote extension of the stifle joint (Boudrieau 2009, Guerrero et al 2011.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, with the intention to develop a more accurate method to evaluate the lever arm of the extensor mechanism, the PLIA was measured and ratio of the lengths of the lines (X/Y) was calculated to allow for the comparison of values between animals of different sizes (Arruda et al 2015). Theoretically, a longer patellar tendon lever arm will lower the required strength of the quadriceps to move the tibia and promote extension of the stifle joint (Boudrieau 2009, Guerrero et al 2011.…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of the patellar ligament insertion angle (PLIA) was also measured according to Arruda et al (2015). A first straight line was drawn from the site of insertion of the patellar ligament at the tibial tuberosity to the tibiofemoral contact point (line X), and a second line was drawn from the site of insertion of the patellar ligament at the tibial tuberosity to the most cranial aspect of the patella (line Y).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mediolateral radiographs were performed with the stifle joint at an angle of approximately 135°, which is the limb support angle of the joint. In the mediolateral radiographs, measurements were taken of the tibial plateau angle and patellar ligament angle in relation to the tibial plateau (Collins et al, 2014, Arruda et al, 2015. The craniocaudal radiographs were taken to confirm the health of the joint during the preoperative period and to evaluate possible joint changes in the postoperative period.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, it was believed that this disease may occur due to the tibial plateau angle (Osmond et al, 2006;Kim et al, 2008). Radiographic exams aid in the evaluation of DJD following rupture, but they are essential for measuring the tibial plateau angle and other angles and measurements of the proximal tibia for surgical planning (Cadmus et al, 2014;Collins et al, 2014;Arruda et al, 2015). A radiographic study showed that dogs with CCL rupture have a greater angle of the tibial plateau than dogs without the disorder (Osmond et al, 2006).…”
mentioning
confidence: 99%